2012
DOI: 10.1155/2012/645178
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons in Various Species of Fishes from Mumbai Harbour, India, and Their Dietary Intake Concentration to Human

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental contaminants which have caused worldwide concerns as toxic pollutant. This study reports the concentrations of 15 PAHs in 5 species of fish samples collected along the harbour line, Mumbai, between 2006 and 2008. Among 5 species of fish investigated, Mandeli, Coilia dussimieri, detected the maximum concentration of PAHs (P < 0.05) followed by Doma, Otolithes ruber. The concentration of total and carcinogenic PAHs ranged from 17.43 to 70.44 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 30 publications
2
17
1
Order By: Relevance
“…As mean bio-concentration of toxicants varies in fish tissues. Correlations between PAHs in the environmental matrixes and in tissues load of contaminants, these can be useful in assessment of exposure to pollutants (Dhananjayan and Muralidharan, 2012). One study found strong gradient of PAH concentration in sediment and mussel (Mytilus edulis and Modiolus modiolus) tissue up to several kilometers away from a ferro-alloy smelter Boese et al (1990).…”
Section: Resultsmentioning
confidence: 99%
“…As mean bio-concentration of toxicants varies in fish tissues. Correlations between PAHs in the environmental matrixes and in tissues load of contaminants, these can be useful in assessment of exposure to pollutants (Dhananjayan and Muralidharan, 2012). One study found strong gradient of PAH concentration in sediment and mussel (Mytilus edulis and Modiolus modiolus) tissue up to several kilometers away from a ferro-alloy smelter Boese et al (1990).…”
Section: Resultsmentioning
confidence: 99%
“…The average dietary intake concentration of PAH through consumption of Sarotheron melanotheron at the studied area (Atlas cove, Lagos) was higher than that reported by Olaji et al [26] at Degele community. It also exceeded that reported by Dhananjayan and Muralidharan [2] in India and Moon et al [33] in Korea. The consumption of Sarotheron melanotheron at the rate of 68.5g/day may adversely affect human health.…”
Section: Resultsmentioning
confidence: 40%
“…Humans are exposed to total hydrocarbon content (THC) through air, water, food, or soil. However, dietary intake has been shown to be a major route for human exposure to petroleum hydrocarbons [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of Tilapia zilli could be a potential source of PAH exposure route among the people at the examined site as fish constitutes a major source of animal protein in their diet (FAO, 1983). Dietary intake has been identified as a major route of human exposure to PAHs (Yu et al, 2014) and recent studies have shown that most human cancers such as prostrate and lung cancer can be attributed to dietary sources (Dhananjayan and Murahdharan, 2012). Nkpa et al (2013) reported PEC values of 0.003 to 0.012 for Tilapia quineesis and 0.002 to 0.011 for Liza falcipines from crude oil polluted water of Ogoni land.…”
Section: Carcinogenic Health Risk Induced By the Consumption Of Tilapmentioning
confidence: 99%